Effectiveness of Music Interventions to Reduce Test Anxiety in Pharmacy Students - Suzanne Galal; Deepti Vyas; Rachelle Kisst Hackett; Ed Rogan; Chloe Nguyen (MDPI AG, 2021)
Background: The main objective of this pilot study was to evaluate the impact of a classroom activity involving music on anxiety associated with preparing for and taking an assessment. Methods: Two hundred and two (202) pharmacy students were randomly assigned to one of two conditions of the experimental study: active music playing (n = 103) versus passive music listening (n = 99). All students completed a pre-test, a mid-test, and a post-test including: an "Attitudes and Perceptions" survey, State-Trait Anxiety Inventory for Adults (STAI Survey), and a knowledge assessment. Data were analyzed to determine the impact each of the music interventions had on students' test anxiety. Results: Both types of musical interventions produced similar results in terms of anxiety reduction. Faced with an upcoming test prior to the musical intervention, average state-trait anxiety scores increased; after the musical intervention, state-trait anxiety scores decreased. Conclusions: The use of music helped to reduce test anxiety, even after one brief musical intervention, regardless of whether students passively listened to music or actively played music.